The Role of TLR4 Asp299Gly and TLR4 Thr399Ile Polymorphisms in the Pathogenesis of Urinary Tract Infections: First Evaluation in Infants and Children of Greek Origin - Panagiota Karananou; Despoina Tramma; Socrates Katafigiotis; Anastasia Alataki; Alexandros Lambropoulos; Efimia Papadopoulou-Alataki (Journal of Immunology Research)
Urinary tract infections are one of the most common and serious bacterial infections in a pediatric population. So far, they have mainly been related to age, gender, ethnicity, socioeconomic level, and the presence of underlying anatomical or functional, congenital, or acquired abnormalities. Recently, both innate and adaptive immunities and their interaction in the pathogenesis and the development of UTIs have been studied. The aim of this study was to assess the role and the effect of the two most frequent polymorphisms of TLR4 Asp299Gly and Thr399Ile on the development of UTIs in infants and children of Greek origin. We studied 51 infants and children with at least one episode of acute urinary tract infection and 109 healthy infants and children. We found that 27.5% of patients and 8.26% of healthy children carried the heterozygote genotype for TLR4 Asp299Gly. TLR4 Thr399Ile polymorphism was found to be higher in healthy children and lower in the patient group. No homozygosity for both studied polymorphisms was detected in our patients. In the group of healthy children, a homozygote genotype for TLR4 Asp299Gly (G/G) as well as for TLR4 Thr399Ile (T/T) was showed (1.84% and 0.92 respectively). These results indicate the role of TLR4 polymorphism as a genetic risk for the development of UTIs in infants and children of Greek origin.